Buffer layer for all-solid-state battery

By introducing a buffer layer with a thickness of 0.5 to less than 10 nm into the all-solid-state battery pack, the problem of rapid aging of the battery pack during circulation is solved, and the maintenance of high energy capacity and the extension of the battery pack life are achieved.

CN119866548APending Publication Date: 2025-04-22SAINT GOBAIN CERAMICS & PLASTICS INC +5
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202380051920.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-07-04
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

All-solid-state battery packs age rapidly during the charging/discharge cycle and are difficult to maintain high energy capacity.

Method used

An all-solid state battery pack design is adopted that includes a buffer layer, where the buffer layer consists of materials such as lithium phosphate (Li3PO4) or oxide, with a thickness controlled between 0.5 and less than 10 nm, and is deposited on the surface of solid electrolyte and electrode materials through vapor deposition techniques such as atomic layer deposition (ALD).

Benefits of technology

The buffer layer provides physical separation, preventing direct electrochemical reactions between the electrolyte and the electrode material, significantly extending the cycle life of the battery pack and maintaining high energy capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005228034340000011
    Figure HDA0005228034340000011
  • Figure HDA0005228034340000021
    Figure HDA0005228034340000021
  • Figure HDA0005228034340000031
    Figure HDA0005228034340000031
Patent Text Reader

Abstract

The present invention relates to an all-solid-state battery (ASSB) comprising: an anode comprising a first solid electrolyte; a cathode composite comprising a second solid electrolyte, a solid electrolyte selected from the first and second solid electrolytes, and at least one buffer layer in contact with a surface of the solid electrolyte, where when the solid electrolyte is the first solid electrolyte, one buffer layer is at an interface of the electrolyte with the cathode, and when the solid electrolyte is the second solid electrolyte, one buffer layer is at least one of the first solid electrolyte and the second solid electrolyte. And when the solid electrolyte is a second solid electrolyte, a buffer layer is at the interface of the electrolyte and the anode, where the first electrolyte is selected from a sulfide solid electrolyte and a lithium oxide solid electrolyte, where the second electrolyte is a halide solid electrolyte, and where the buffer layer has a thickness of from 0.5 nm to less than 10 nm. The invention also relates to an anode assembly, a cathode assembly and an electrolyte assembly comprising at least one buffer layer. The invention also relates to a method for producing an ASSB or component according to the invention, in which the buffer layer is deposited by a vapor deposition-based method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is in the field of all-solid-state rechargeable batteries (ASSBs) and in particular relates to their individual components, such as anodes, cathodes and solid electrolytes, and the interactions between said components. Background Art

[0002] ASSBs are of particular interest as an alternative to conventional lithium-ion battery packs, not least because they raise fewer safety concerns and have higher capacities.

[0003] To achieve ASSB, a solid electrolyte is used instead of the liquid electrolyte in lithium-ion battery packs. ASSB also uses a Li-metal anode and high-energy NMC cathode particles that are incorporated into the solid electrolyte.

[0004] Such solid electrolytes are selected, for example, from lithium thiophosphate (β-Li3PS4, LPS), argyrodite (Li6PS5Cl), such as described by HJ. Deiseroth et al. in: “Li6PS5X: a class Of crystalline Li-rich solids with an unusually high Li+mobility.” Angew. Chem. Int. Ed., 47 (2008), pp. 755-758, and halides, such as Li3InCl6, as described in: X. Li et al. “Air-stable Li3InCl6electrolyte with high voltage compatibility for all-solid-state batteries.” Energy Environ. Sci., 2019, 12, pp. 2665-267; Schmidt, MO et al. “Zur Kristallstruktur von Li3InCl6.” Zeitschrift für Anorg. und Allg. Chemie 1999, 625(4), 539-540; and G. Meyer, et al., "Handbook on the Physics & Chemistry of Rare Earths", V. 28, Chapter 177, 2000 Elsevier Sci.

[0005] However, the main drawback of these compounds is their chemical and electrochemical interactions with electrode materials.

[0006] Halide solid electrolytes are of particular interest because they show good ionic conductivity (higher than 2 mS / cm), high electrochemical stability against oxidation on the cathode side and better compactness (deformability) than other solid inorganic electrolytes.

[0007] However, although halide solid electrolytes show good electrochemical resistance to high-energy NMC cathodes, they are not compatible with Li-metal anodes, especially Li-metal and Li x Si y Incompatible, it reduces the electrolyte to the metallic state.

[0008] Moreover, sulfide electrolytes, although having high ionic conductivity and being compatible with Li-metal anodes, are electrochemically unstable to high-energy NMC cathodes. Therefore, during the operation of a battery pack in which the electrolyte is a sulfide electrolyte, the capacity degradation of the sulfide-based electrolyte is inevitable.

[0009] There are two other inconveniences associated with sulfide electrolytes: the generation of toxic gases (HS) if the electrolyte is accidentally exposed to moisture, and the low surface contact wetting of NMS particles, which necessitates the continuous application of relatively high external compressive pressures to maintain the integrity of the battery interlayer.

[0010] These chemical and electrochemical interactions lead to rapid aging of ASSBs.

[0011] T. F. Marchini, G. Rousse, R. Dugas, and J.-M. Tarascon, “In Search Of the Best Solid Electrolyte-Layered Oxide Pairing for Assembling Practical All-Solid-State Batteries.” ACS Appl. Energy Mater. 2021, NV. 4, N 12, PP. 13575-13585, https: / / doi.org / 10.1021 / acsaem.1c02187, address the compatibility issue of solid electrolytes with ASSB electrodes by preparing heterostructured ionic conductors coupled with halide-based cathodes separated from the anode by an ionic conductor of the more anode-stable argyrodite or LPS type.

[0012] However, the direct halide-argyrodite interface was shown to be unstable, which limited the cycling performance of ASSBs prepared with the heterostructure electrolyte. Summary of the invention

[0013] Technical issues

[0014] Therefore, the present invention provides a solution to the technical problem of preventing rapid aging of all-solid-state batteries while maintaining high energy capacity during charge / discharge cycles.

[0015] Solutions to technical problems

[0016] Therefore, according to a first aspect, the present invention relates to an all-solid-state battery pack, comprising:

[0017] - an anode comprising an anode active material and a first solid electrolyte,

[0018] - a cathode composite material comprising a cathode active material and a second solid electrolyte,

[0019] - a solid electrolyte comprising a solid electrolyte material selected from the group consisting of a first and a second solid electrolyte, and

[0020] at least one buffer layer, in particular one or two buffer layers, is in contact with the surface of the solid electrolyte material, wherein

[0021] When the solid electrolyte material is a first solid electrolyte, there is a buffer layer at the interface between the electrolyte and the cathode composite material, and

[0022] When the solid electrolyte material is a second solid electrolyte, there is a buffer layer at the interface between the electrolyte and the anode,

[0023] wherein the first electrolyte is selected from a sulfide solid electrolyte and a lithium oxide solid electrolyte,

[0024] wherein the second electrolyte is a halide solid electrolyte, and

[0025] The thickness of the buffer layer is 0.5 to less than 10 nm.

[0026] According to a second aspect, the invention also relates to an assembly comprising:

[0027] - a solid electrolyte comprising a solid electrolyte material selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte and a lithium oxide solid electrolyte, and

[0028] at least one buffer layer, in particular one or two buffer layers, which are in contact with the surface of the solid electrolyte material,

[0029] The thickness of the buffer layer is 0.5 to less than 10 nm.

[0030] Hereinafter, this second aspect may be referred to as a "solid electrolyte assembly".

[0031] According to a third aspect, the present invention also relates to an assembly comprising:

[0032] - an anode comprising an anode active material and a solid electrolyte selected from a sulfide solid electrolyte and a lithium oxide solid electrolyte, and

[0033] - a buffer layer in contact with the surface of the anode composite,

[0034] The thickness of the buffer layer ranges from 0.5 to less than 10 nm.

[0035] This third aspect may hereinafter be referred to as the "anode assembly".

[0036] According to a fourth aspect, the present invention also relates to an assembly comprising:

[0037] - a cathode composite material comprising a cathode active material and a halide solid electrolyte, and

[0038] - a buffer layer in contact with the surface of the cathode composite material,

[0039] The thickness of the buffer layer is 0.5 to less than 10 nm.

[0040] This fourth aspect may hereinafter be referred to as a "cathode assembly".

[0041] Both the anode and the cathode are electrodes, namely the negative electrode and the positive electrode respectively. The third and fourth aspects mentioned above may be collectively referred to as "electrode assemblies" hereinafter.

[0042] The assembly or all-solid-state battery (ASSB) according to the present invention allows providing an ASSB having a high energy capacity and a good retention of its capacity.

[0043] Finally, the present invention also relates to a method for producing an all-solid-state battery according to the invention or a component according to the invention, wherein the buffer layer is deposited onto at least one substrate selected from a solid electrolyte, an anode composite and a cathode composite by a method based on vapor deposition, such as physical vapor deposition, chemical vapor deposition or by atomic layer deposition, preferably by atomic layer deposition.

[0044] Advantages of the present invention

[0045] In fact, the buffer layer allows to provide a physical separation between the electrolyte and the electrode material, with which the electrolyte is incompatible, which prevents any direct electrochemical reaction between said compounds.

[0046] Furthermore, it is apparent from this description that buffer layers implemented in accordance with the present invention have good compatibility with most solid electrolytes, particularly halides and sulfides, and have acceptable ionic conductivity.

[0047] The resistance of the buffer layer is particularly advantageous when the thickness of the layer is from 0.5 nm to less than 10 nm.

[0048] Implementing a method based on vapor deposition in the method according to the invention allows controlling the thickness of the deposited buffer layer. In particular, the use of atomic layer deposition (ALD) allows providing incremental atomic layers and thus controlling the thickness of the buffer layer with extremely high precision.

[0049] The present invention realizes the best performance of sulfide-based electrolytes on the anode side and halide-based electrolytes on the cathode side. It provides a cost-effective solution that is easily implemented by known deposition techniques to obtain a complete long-lasting high-capacity all-solid-state battery pack. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 Schematic diagram of an implementation scheme of a procedure for introducing a buffer layer onto the surface of a solid electrolyte, comprising 4 steps a), b), c) and d). In step a), a solid electrolyte powder (1) is pressed between a moving piston (2) and a fixed piston (2′) within a cell body (3). In step b), the moving piston (2) and the fixed piston (2′) are removed, and a dense solid electrolyte (1′) of about 300 μm thick is obtained. In step c), a buffer layer (4) is processed on the dense solid electrolyte (1′) by atomic layer deposition (ALD) technology. At the end of step c), a buffer layer (4) having a thickness of about 0.5 nm to about 10 nm is obtained. In step d), a positive electrode (5) is placed on the coated side of the dense solid electrolyte (1′), i.e., on one side of the buffer layer (4), while a negative electrode (6) is placed on the uncoated side of the dense solid electrolyte (1′) for assembling a complete all-solid-state battery pack.

[0051] Figure 2 Nyquist plot of real impedance (Re(Z), ohm) vs. imaginary impedance (Z′, ohm) comparing pristine Li6PS5Cl with single-sided Li3PO4-coated Li6PS5Cl solid electrolyte, where the coated electrolyte has a 1 nm thick buffer layer.

[0052] Figure 3 The electrochemical performance of the battery according to Example 1 of the present invention at room temperature at C / 20 is shown, for a) and b) it contains 2nm thickness of Li3PO4, and for c) and d) it contains 1nm thickness of Li3PO4. a) and c) represent constant current cycles. b) and d) are graphs of discharge capacity (milliampere-hour, mAh) vs. cycle number, showing the capacity retention of the battery.

[0053] Figure 4Figure 1 shows the electrochemical performance of a cell according to a comparative example at C / 20 at room temperature under argon and in a gastight cell under ambient atmosphere. a) represents constant current cycling. b) is a graph of discharge capacity (milliampere hours, mAh) vs. cycle number, showing the change in discharge capacity with respect to the number of cycles in the cell.

[0054] Figure 5 Figure 2 shows the electrochemical performance of a battery according to Example 2 of the present invention at room temperature at C / 20, the battery having two 1 nm thick Li3PO4 buffer layers. a) represents the constant current cycling of the battery. b) is a graph of discharge capacity (milliampere-hour, mAh) vs. cycle number, illustrating the capacity retention of the battery.

[0055] Figure 6 For the Li6PS5Cl solid electrolyte coated with a 10 nm thick Li3PO4 buffer layer (i.e., Comparative Example 2 ( Figure 6 a)) and for the Li6PS5Cl solid electrolyte coated with a 10 nm thick Al2O3 buffer layer (ie, Comparative Example 3 ( Figure 6 b) Nyquist plot of real impedance (Re(Z), ohms) vs. imaginary impedance (Z′, ohms) established.

[0056] Figure 7 According to Comparative Example 2 ( Figure 7 a) and Comparative Example 3 ( Figure 7 b) Constant current cycling of the battery.

[0057] Detailed description of specific implementation scheme

[0058] The assembly or all-solid-state battery according to the present invention comprises at least one solid electrolyte selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte and a lithium oxide solid electrolyte, as described in detail below.

[0059] The electrolyte assembly according to the present invention includes a solid electrolyte selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte, and a lithium oxide solid electrolyte.

[0060] The anode assembly according to the present invention includes a solid electrolyte selected from a sulfide solid electrolyte and a lithium oxide solid electrolyte.

[0061] The cathode assembly according to the present invention comprises a halide solid electrolyte.

[0062] Halide solid electrolyte

[0063] The halide solid electrolyte can be represented by the following chemical formula

[0064] M 3-z (Me k+ ) f X3-z+k*f

[0065] Where -3≤z≤3,

[0066] k is the valence of Me, and 2≤k<6, 0≤f≤1;

[0067] - M includes alkali metal elements, especially Li;

[0068] -Me includes metals other than alkali metals, and

[0069] -X is halogen.

[0070] In certain embodiments, f is not equal to zero.

[0071] In a specific embodiment, Me includes more than one metal element, and k may be the average value of the total valence of each metal element. For example, when Me includes equimolar amounts of trivalent elements and tetravalent elements, k=(3+4) / 2=3.5. In particular, k may be 2, 3, 4 or 5.

[0072] It should be understood that atomic vacancies may exist within the unit cell of the halide solid electrolyte. In this case, the atomic vacancy in the formula of the solid halide electrolyte may be represented as M 3-z (Me k+ ) f·y X 3-z+k*f , where · represents an atomic vacancy within a single cell, and y is the number of empty atomic positions. In a specific embodiment, y may be f*(k-1).

[0073] In a specific embodiment, M may include Li, Na, K, Rb, Cs or any combination thereof. For example, M may include at least one of Li and Na or a combination thereof. On the other hand, M may consist of at least one alkali metal element. For example, M may consist essentially of at least one alkali metal element selected from Li, Na, K, Rb and Cs. In another example, M may consist of Li. In yet another example, M may consist of a combination of Li and at least one of Na, K, Rb and Cs. In another example, M may consist of Na and at least one of Cs and Rb. In another example, M may consist of at least one of Na and Cs.

[0074] In a specific embodiment, Me can include alkaline earth metal elements, rare earth elements, 3d transition metals, elements selected from the following: Zr, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, Te, In, Bi, Al, Ga and any combination thereof. For example, Me can include alkaline earth metals, and the alkaline earth metals include Ba, Mg, Ca and Sr or any combination thereof. In another example, Me can include rare earth elements, and in particular Me can be composed of at least one rare earth element. Rare earth elements can be selected from Y, Sc, Ce, Gd, Er, La, Yb and combinations thereof. In another example, Me can include 3d transition metals, especially selected from Zn, Cu, V and any combination thereof. In yet another example, Me can include elements selected from the following: Zr, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, Te, In, Bi, Al, Ga and any combination thereof.

[0075] In a specific embodiment, X may include halogen, which is particularly selected from Cl, Br, I and any combination thereof. In an example, X may include at least one of Cl and Br. Preferably, X may consist of Cl, Br or any combination thereof.

[0076] Therefore, in an embodiment of the present invention, the all-solid-state battery according to the present invention, the cathode assembly according to the present invention, or the electrolyte assembly according to the present invention may include a halide solid electrolyte of the formula:

[0077] M 3-z (Me k+ ) f X 3-z+k*f

[0078] Where -3≤z≤3, 2≤k<6, 0≤f≤1;

[0079] - M includes alkali metal elements, especially Li;

[0080] -Me includes divalent, trivalent, tetravalent, pentavalent or hexavalent metal elements or any combination thereof, in particular Me is selected from:

[0081] i. Alkaline earth metals, including Ba, Mg, Ca, Sr,

[0082] ii Rare earth elements such as Y, Sc, Ce, Gd, Er, La, Yb and combinations thereof,

[0083] iii.3d transition metals such as Zn, Cu, V and

[0084] iv. an element selected from Zr, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, Te, In, Bi, Al, Ga and

[0085] v. any combination thereof, and

[0086] -X is halogen, in particular selected from Cl, Br, I and any combination thereof;

[0087] Preferably, the halide solid electrolyte is Li3InCl6.

[0088] In a specific embodiment, the halide solid electrolyte may be composed of Li 3-z Me k+ X 3-z+k When z is not 0, the complex metal halide can be non-stoichiometric. When z is 0, the complex metal halide can be stoichiometric. For example, -0.95≤z≤0.95. In another example, Me includes Y, Gd, Yb, In, Sc, Zn, Mg, Ca, Ba, Sn, or a combination thereof, and X is Cl, Br, or a combination thereof.

[0089] In one specific embodiment, the solid halide electrolyte may be represented by Li3MeBr6. In another specific embodiment, the solid halide electrolyte may be represented by Li3MeCl6. In these embodiments, Me may be composed of at least one of the above-mentioned metal elements, with a valence of 3. Me may include at least one of the above-mentioned metal elements, wherein the average valence state of at least one of the metal elements is 3.

[0090] In another specific embodiment, the solid halide electrolyte may consist of Li, Y, and at least one of Cl and Br. For example, the solid halide electrolyte may consist of Li, Y, and Cl. In another example, the solid halide electrolyte may consist of Li, Y, and Br. In yet another example, the solid halide electrolyte may consist of Li, Y, Cl, and Br. In a specific example, the solid halide electrolyte may consist of Li 3x Y 1-x Cl3 or Li 3x Y 1-x Br3 means, where 0 <x≤0.5。

[0091] In another specific embodiment, the solid halide electrolyte may be composed of Li, Gd, and at least one of Cl and Br. For example, the solid halide electrolyte may be composed of Li, Gd, and Cl. In another example, the solid halide electrolyte may be composed of Li, Gd, and Br. In yet another example, the solid halide electrolyte may be composed of Li, Gd, Cl, and Br. In a specific example, the solid halide electrolyte may be composed of Li 3x G 1-x Cl3 or Li 3x G 1-xBr3 represents, where 0.01≤x<1.

[0092] In another specific embodiment, the solid halide electrolyte may consist of Li, In, and at least one of Cl and Br. For example, the solid halide electrolyte may consist of Li, In, and Cl. In another example, the solid halide electrolyte may consist of Li, In, and Br. In yet another example, the solid halide electrolyte may consist of Li, In, Cl, and Br. In a specific example, the solid halide electrolyte may consist of Li 3x In1- x Cl3 or Li 3x In 1-x Br3 represents, where 0≤x<0.5.

[0093] The solid halide electrolyte can be selected from Li3InCl6, Li3InBr6, Li3YCl6, Li3YBr6, Li 2.7 Y 0.7 Zr 0.3 Cl6、Li 2.8 Y 0.8 Sn 0.2 Cl6、Li 3.2 Y 0.8 Zn 0.2 Cl6、Li 3.2 Y 0.8 Mg 0.2 Cl6、Li3Y 1 / 3 Zr 1 / 3 Mg 1 / 3 Cl6、Li3Y 1 / 3 Sn 1 / 3 Mg 1 / 3Cl6、Li3Y 1 / 3 Zr 1 / 3 Zn 1 / 3 Cl6、Li 2.95 Na 0.05 YBr6、Li 2.95 K 0.05 YBr6、Li 2.95 Cs 0.05 YBr6、Li3Y 0.7 G 0.3 Br6、Li3Y 0.8 Yb 0.2 Br6、Li3Y 0.9 La 0.1 Br6、Li 2.9 Y 0.9 Ce 0.1 Br6、Li3In 0.5 Y 0.5Cl6 or Li3Y(Cl,Br)6.

[0094] Sulfide solid electrolyte

[0095] The sulfide solid electrolyte suitable for use in the present invention may include, for example, lithium sulfide, silicon sulfide, phosphorous sulfide, boron sulfide, or a combination thereof.

[0096] Examples of the sulfide solid electrolyte may include at least one of the following: Li2S-P2S5, Li2S-P2S5-LiX (wherein X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2--p2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are both positive numbers, and Z represents any one of Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein P and q are each positive numbers, and M represents at least one of P, Si, Ge, B, Al, Ga or In).

[0097] Sulfide solid electrolytes can also be of the general formula Li 7-x PS 6-x X x Preferably, the sulfide solid electrolyte is an argyrodite of formula Li6PS5Cl.

[0098] The sulfide solid electrolyte may also be a thiophosphate, such as thio-LISICON, for example, selected from (Li) 4- x Ge 1-x P x S4, wherein x is 0 to 1, Li7P2S8I and Li2S-P2S5.

[0099] For example, the sulfide solid electrolyte may include Li 2 S and P 2 S 5. When the sulfide-based solid electrolyte material constituting the sulfide-based solid electrolyte includes Li 2 S—P 2 S 5 , the molar ratio of Li 2 S to P 2 S 5 may be, for example, 50:50 to 90:10.

[0100] Therefore, in an embodiment of the present invention, the all-solid-state battery according to the present invention, the anode assembly according to the present invention or the electrolyte assembly according to the present invention may include a selected from the formula Li 7-x PS 6-x X x A sulfide solid electrolyte of a thiophosphate and argyrodite, wherein 0≤X≤2, and X is a halide, in particular selected from Cl, Br and I, preferably the first solid electrolyte is selected from argyrodite, and even more preferably Li6PS5Cl.

[0101] Lithium oxide solid electrolyte

[0102] The lithium oxide solid electrolyte suitable for the present invention may include, for example, NASICON, perovskite, LISICON, garnet, or a combination thereof.

[0103] Therefore, in an embodiment of the present invention, the all-solid-state battery according to the present invention, the anode assembly according to the present invention or the electrolyte assembly according to the present invention may include a lithium oxide solid electrolyte selected from NASICON such as LiTi2(PO4)3; perovskite such as (LaLi)TiO3; LISICON such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; garnet such as Li7La3Zr2O 12 , in particular the lithium oxide solid electrolyte is garnet, preferably Li7La3Zr2O 12 .

[0104] anode

[0105] In the all-solid-state battery or anode assembly according to the present invention, the anode comprises an anode active material and a solid electrolyte selected from the sulfide solid electrolyte and the lithium oxide solid electrolyte as described above. In particular, the anode may comprise particles comprising the sulfide solid electrolyte, preferably consisting of the sulfide solid electrolyte.

[0106] The negative electrode active material is a material that can store and release metal ions, particularly alkali metal ions such as Li or Na ions.

[0107] As the anode active material metal, carbon, oxide or nitride can be used.

[0108] The metal suitable for use as the anode active material may be a single metal or an alloy, such as lithium metal or a lithium alloy. The metal suitable for use as the anode active material may be selected from silicon, tin, silicon compounds, tin compounds, lithium and lithium alloys.

[0109] Examples of carbon suitable for use as the anode active material include natural graphite, coke, developing carbon, carbon fiber, spherical carbon, artificial graphite, and amorphous carbon.

[0110] Therefore, the anode active material may be selected from

[0111] - oxides,

[0112] - nitrides,

[0113] - Carbon such as natural graphite, coke, grown carbon, carbon fiber, spherical carbon, artificial graphite and amorphous carbon,

[0114] - metals such as silicon, tin, sodium or lithium, their compounds and their alloys,

[0115] In particular, the anode active material is selected from silicon, tin, lithium, their compounds and their alloys, such as Li x In y , wherein x is 0-1, and y is 0-1, preferably the anode active material is Li 0.5 In.

[0116] The anode active material may be present in the ASSB or anode assembly according to the present invention in the form of particles. The median diameter of the anode active material particles may be 0.1 μm to 100 μm. Preferably, the median diameter of the anode active material particles is greater than the median diameter of the sulfide solid electrolyte particles.

[0117] The anode may include

[0118] - 50-70 wt%, and preferably 60 wt% Li 0.5 In, and

[0119] - 30-50 wt %, and preferably 40 wt % of a sulfide solid electrolyte.

[0120] The thickness of the anode in the ASSB or assembly according to the invention may be from 10 μm to 500 μm.

[0121] A buffer layer is deposited on the anode assembly according to the invention. In particular, the buffer layer deposited on the anode assembly according to the invention comprises, in particular consists of, a buffer material selected from the group consisting of: lithium phosphates such as Li3PO4 or lithium phosphorus oxynitride; NASICONs such as LiTi2(PO4)3; perovskites such as (LaLi)TiO3; LISICONs such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; garnet such as Li7La3Zr2O 12 ; Preferably, the buffer layer comprises Li3PO4, in particular consists of Li3PO4.

[0122] cathode

[0123] In the all-solid-state battery or cathode assembly according to the present invention, the cathode composite material comprises a cathode active material and a halide solid electrolyte as described above. In particular, the cathode may include particles comprising, preferably consisting of, a halide solid electrolyte.

[0124] The cathode active material is a material capable of storing and releasing metal ions, particularly alkali metal ions such as Li or Na ions.

[0125] As cathode active materials, doped or undoped, coated or uncoated transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluoride oxides, transition metal oxysulfides, transition metal oxynitrides and transition metal oxides containing lithium can be used. In particular, the cathode active material can be a transition metal oxide, such as lithium cobalt oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese cobalt oxide. Transition metal oxides suitable for use as cathode active materials can be, for example, LiNi 0.6 Mn 0.2 Co 0.2 O2, Li(NiCoAl)O2 and LiCoO2. Preferably, the cathode active material is of the formula LiNi 0.6 Mn 0.2 Co 0.2 Transition metal oxides of O2.

[0126] The cathode active material may be present in the ASSB or cathode assembly according to the present invention in the form of particles. The median diameter of the negative electrode active material particles may be 0.1 μm to 100 μm. Preferably, the median diameter of the negative electrode active material particles is greater than the median diameter of the solid electrolyte particles (sulfide, halide or lithium oxide).

[0127] The cathode composite material may include

[0128] 55 to 75% by weight, in particular 60 to 70% by weight, and preferably 66.7% by weight of cathode active material,

[0129] 20 to 40% by weight, in particular 25 to 30% by weight, and preferably 28.6% by weight of a halide solid electrolyte, and optionally

[0130] 1 to 10% by weight, in particular 2 to 7% by weight and preferably 4.8% by weight of an electron-conducting carbon compound.

[0131] The thickness of the anode in the ASSB or assembly according to the invention may be from 10 μm to 500 μm.

[0132] The buffer layer is deposited on the cathode assembly according to the invention. In particular, the buffer layer deposited on the cathode assembly according to the invention comprises the following buffer material, in particular consists of the following buffer material: the buffer material is selected from lithium phosphate such as Li3PO4 or lithium phosphorus oxynitride; lithium nitride; NASICON such as LiTi2(PO4)3; perovskite, such as (LaLi)TiO3; LISICON, such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; and garnet such as Li7La3Zr2O 12 ; Preferably, the buffer layer comprises Li3PO4, in particular consists of Li3PO4.

[0133] At least one of the anode and the cathode may include an electron conductor compound selected from natural or artificial graphite, graphene, carbon nanotubes, acetylene black, Ketjen black, activated carbon, fluorinated carbon, metal powder, conductive whiskers, conductive metal oxides, conductive polymers, metal fibers or carbon fibers. Preferably, the electron conductor is vapor-grown carbon fibers.

[0134] Buffer layer

[0135] The ASSB or assembly according to the invention comprises at least one buffer layer. When the assembly is an electrode assembly according to the invention, it may comprise at most one buffer layer. However, in the case of an ASSB or electrolyte assembly according to the invention, it may comprise one or two buffer layers. When the object of the invention comprises two buffer layers, these layers are in contact with two opposite faces of the solid electrolyte comprised in the object of the invention.

[0136] The buffer layer or separation layer is intended to prevent direct electrochemical or chemical reactions between the two components of the ASSB according to the invention. Thus, the buffer layer may prevent reactions between: sulfide and halide solid electrolytes, halide solid electrolyte and anode and / or sulfide solid electrolyte and cathode.

[0137] To meet this requirement, the buffer layer needs to have good electrochemical stability towards the lithium metal anode and solid electrolyte, especially halide solid electrolyte, sulfide solid electrolyte and lithium oxide solid electrolyte.

[0138] Thus, the buffer layer may include an oxide-based or fluoride-based compound that is chemically inert to the halide, sulfide, and / or lithium oxide solid electrolyte.

[0139] In a specific embodiment of the present invention, the buffer layer comprises a metal oxide, such as Al2O3, ZnO, ZrO2, TiO2, preferably, the buffer layer comprises Al2O3.

[0140] In another embodiment of the present invention, the buffer layer comprises an ion conductor selected from the group consisting of: lithium phosphate such as Li3PO4 or lithium phosphorus oxynitride; lithium nitride; NASICON such as LiTi2(PO4)3; perovskite such as (LaLi)TiO3; LISICON such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; garnet such as Li7La3Zr2O 12 ; and LiAlO2.

[0141] Thus, in an ASSB or component according to the invention, the buffer layer may comprise, in particular consist of, a buffer material selected from the group consisting of: lithium phosphates such as Li3PO4 or lithium phosphorus oxynitride; lithium nitride; NASICONs such as LiTi2(PO4)3; perovskites such as (LaLi)TiO3; LISICONs such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; garnet such as Li7La3Zr2O 12 and Al2O3, more particularly the buffer layer comprises, in particular consists of: Li3PO4 or Al2O3; preferably, the buffer layer comprises Li3PO4, in particular consists of Li3PO4.

[0142] In a specific embodiment of the present invention, the buffer layer comprises, in particular consists of, a buffer material selected from the group consisting of: lithium phosphate such as Li3PO4 or lithium phosphorus oxynitride; lithium nitride; NASICON such as LiTi2(PO4)3; perovskite such as (LaLi)TiO3; LISICON such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; and garnet such as Li7La3Zr2O 12 ; Preferably, the buffer layer comprises Li3PO4, in particular consists of Li3PO4.

[0143] Li3PO4 is preferred as a buffer material because it has good compatibility with both sulfide and halide solid electrolytes and acceptable Li + Ionic conductivity.

[0144] Furthermore, although the ionic conductivity of the buffer layer may be acceptable, it is still lower than that of either sulfide or halide solid electrolytes.

[0145] However, limiting the thickness of the buffer layer to less than 10 nm still allows for the prevention of reactions as mentioned above, while also alleviating the limiting aspect of the ionic conductivity of the buffer layer.

[0146] In other words, a buffer layer at least 10 nm thick produces an ASSB with poor electrochemical properties.

[0147] On the other hand, a buffer layer finer than 0.5 nm may not adequately prevent the reaction between the two components of the ASSB mentioned herein.

[0148] Therefore, in the ASSB or assembly according to the present invention, the thickness of the buffer layer is 0.5 to less than 10 nm.

[0149] In a specific embodiment, the thickness of the buffer layer is from 0.75 to 5 nm, and preferably from 1 to 2 nm.

[0150] Preparation method

[0151] In order to meet the thickness requirements of the buffer layer in the ASSB or assembly according to the present invention, the buffer layer may be deposited onto the surface by a vapor deposition based method.

[0152] Such vapor deposition-based methods are, for example, physical vapor deposition (PVD) and chemical vapor deposition (CVD).

[0153] The buffer layer can also be deposited by atomic layer deposition (ALD). ALD allows a particularly fine adjustment of the thickness of the buffer layer.

[0154] Therefore, the present invention also relates to a method for manufacturing an all-solid-state battery pack or component according to the present invention, wherein the buffer layer is deposited onto at least one substrate selected from a solid electrolyte, an anode composite material and a cathode composite material by a vapor deposition-based method such as physical vapor deposition, chemical vapor deposition or by atomic layer deposition, preferably by atomic layer deposition.

[0155] In a particular embodiment of the method according to the invention, the buffer layer is deposited on a powder substrate or on a dense substrate.

[0156] According to this embodiment, the powder substrate, before its densification, may be a component of an assembly according to the invention or a component of an ASSB according to the invention. Thus, the powder substrate may be a solid electrolyte, anode and / or cathode composite material.

[0157] When the buffer material is deposited on the powder substrate, a coated powder substrate is obtained. Once the coated powder substrate is densified, the buffer material constitutes a buffer layer on at least one surface of the resulting densified material.

[0158] In order to provide lithium in the buffer layer, for example when the buffer layer is Li3PO4, a precursor of the formula LiOR can be used as a precursor, wherein R is a C1-C6 alkyl group, preferably lithium tert-butoxide is used as a precursor to provide lithium.

[0159] In order to provide phosphate in the buffer layer, for example when the buffer layer is Li3PO4, a precursor of the formula OP(OR)3 can be used as a precursor, wherein R is a C1-C3 alkyl group, preferably OP(OH3)3 is used as a precursor.

[0160] In order to provide aluminum in the buffer layer, for example when the buffer layer is Al2O3, a precursor of the formula AlR3 can be used as a precursor, wherein R is a C3-C1 alkyl group, preferably Al(CH3)3 is used as a precursor.

[0161] To provide oxygen in the buffer layer, for example when the buffer layer is Al2O3, ozone can be used as a precursor.

[0162] In one specific embodiment of the present invention, the buffer layer is deposited by atomic layer deposition, and the atomic layer deposition reactor is set at the following temperature:

[0163] -85°C to 185°C, particularly 100°C to 170°C, and preferably 150°C, or

[0164] -200°C to 400°C, particularly 250°C to 350°C, and preferably at 300°C.

[0165] The electrodes and electrolytes of the ASSB or assembly according to the invention are prepared according to methods known to those skilled in the art and are illustrated in the following examples.

[0166] Comparative Example 1

[0167] Synthesis of solid sulfide electrolytes

[0168] Li6PS5C1 was synthesized by annealing a stoichiometric mixture of Li2S, P2S5, and LiCl in an Al2O3 crucible.

[0169] The powder mixture was placed in a crucible and sealed in a quartz tube under vacuum, and finally annealed at 550° C. for 72 hours at a heating rate of 5° C. / min, followed by natural cooling to room temperature.

[0170] Synthesis of a solid halide electrolyte

[0171] Li3InCl6 was prepared by dissolving InCl3 and LiCl in distilled water. The precursor was placed at room temperature with continuous stirring overnight, and the resulting clear solution was naturally dried at 100°C.

[0172] A white powder was obtained and was subsequently dried first at 100° C. for 24 hours and then at 200° C. for 24 hours under dynamic vacuum (P<1 mbar) and subsequently cooled naturally to room temperature.

[0173] Synthesis of cathode composites

[0174] By LiNi 0.6 Mn 0.2 Co 0.2 The cathode composite material was prepared from a hang-ground mixture of O2(NMC622):Li3InCl6:VGCF (weight ratio 70:30:5).

[0175] Battery Pack Components

[0176] The battery pack assembly was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0177] The assembly procedure was carried out in a glove box under argon atmosphere ([O 2 ]<1 ppm, [H 2 O]<1 ppm).

[0178] The two-electrode cell was assembled as follows.

[0179] 16 to 18 mg / cm 2 The cathode composite material (NMC622 / Li3InCl6 / VGCF) was spread on the surface of the Li6PS5Cl solid electrolyte, and then Li 0.5 A mixture of In and Li6PS5Cl (in a weight ratio of 60:40) was added to the opposite side of the Li6PS5Cl solid electrolyte pellet as a counter electrode.

[0180] Finally, the entire stack is further heated to 4 t / cm 2 Densification for 15 minutes. After compression, 1t / cm 2 of pressure was applied to the fully assembled cell for electrochemical studies.

[0181] Embodiment 1 according to the present invention

[0182] The solid sulfide electrolyte, solid halide electrolyte, and cathode composite were prepared as described above for Comparative Example 1.

[0183] Atomic Layer Deposition

[0184] Nano-thick Li3PO4 films were grown in a Picosun R200 advanced ALD reactor at an argon pressure of about 2 mbar. Argon was used as carrier and purge gas.

[0185] Lithium tert-butyl oxide (LiOtBu) and trimethyl phosphate (TMPO) precursor were used as lithium and phosphate sources, respectively. LiOtBu precursor was purchased from Strem Chemicals (purity 98%), while TMPO precursor was purchased from Sigma-Aldrich (purity 99%). The sublimation temperatures were adapted to be 185°C and 85°C, respectively.

[0186] The temperature of the ALD reactor was set to 150°C, and the number of ALD cycles was modified to adjust the thickness of the buffer layer. 17 ALD cycles were performed to obtain a 1 nm thick buffer layer. 34 ALD cycles were performed to obtain a 2 nm thick buffer layer.

[0187] TMPO and subsequently LiOtBu were alternately pulsed into the chamber with pulse times of 6 s and 3 s, respectively, separated by an 8 s argon purge.

[0188] Li6PS5Cl solid electrolyte pellets were obtained, one side of which was coated with Li3PO4.

[0189] Battery Pack Assembly

[0190] The battery pack assembly was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0191] The assembly procedure was carried out in a glove box under argon atmosphere ([O 2 ]<1 ppm, [H 2 O]<1 ppm).

[0192] The two-electrode cell was assembled as follows.

[0193] 16 to 18 mg / cm 2 The cathode composite material (NMC622 / Li3InCl6 / VGCF) was spread onto the Li3PO4 coated surface of the Li6PS5Cl solid electrolyte, and then Li 0.5 A mixture of In and Li6PS5Cl (in a weight ratio of 60:40) was added to the uncoated side of the Li6PS5Cl solid electrolyte pellets as a counter electrode.

[0194] Finally, the entire stack is further heated to 4 t / cm 2 Densification for 15 minutes. After compression, 1t / cm 2 of pressure was applied to the fully assembled cell for electrochemical studies.

[0195] Comparative Example 2

[0196] The solid sulfide electrolyte, solid halide electrolyte, and cathode composite were prepared as described above for Comparative Example 1.

[0197] Atomic Layer Deposition

[0198] Nanometer-thick Li3PO4 films were grown in an R200 advanced ALD reactor from Picosun at an argon pressure of about 2 mbar. Argon was used as carrier and purge gas.

[0199] Lithium tert-butyl oxide (LiOtBu) and trimethyl phosphate (TMPO) precursor were used as lithium and phosphate sources, respectively. LiOtBu precursor was purchased from Strem Chemicals (purity 98%), while TMPO precursor was purchased from Sigma-Aldrich (purity 99%). The sublimation temperatures were adapted to be 185°C and 85°C, respectively.

[0200] The temperature of the ALD reactor was set at 150°C with a growth rate of 0.6 Angstroms / cycle. Thus 167 cycles were performed to obtain a 10 nm thick buffer layer.

[0201] TMPO and subsequently LiOtBu were alternately pulsed into the chamber with pulse times of 6 s and 3 s, respectively, separated by an 8 s argon purge.

[0202] Li6PS5Cl solid electrolyte pellets were obtained, one side of which was coated with Li3PO4.

[0203] Battery Pack Assembly

[0204] The battery pack assembly was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0205] The assembly procedure was carried out in a glove box under argon atmosphere ([O 2 ]<1 ppm, [H 2 O]<1 ppm).

[0206] The two-electrode cell was assembled as follows.

[0207] 16 to 18 mg / cm 2 The cathode composite material (NMC622 / Li3InCl6 / VGCF) was spread onto the Li3PO4-coated surface of the Li6PS5Cl solid electrolyte, and then Li 0.5 A mixture of In and Li6PS5Cl (in a weight ratio of 60:40) was added to the uncoated side of the Li6PS5Cl solid electrolyte pellets as a counter electrode.

[0208] Finally, the entire stack is further heated to 4 t / cm 2 Densification for 15 minutes. After compression, 1t / cm 2 of pressure was applied to the fully assembled cell for electrochemical studies.

[0209] Embodiment 2 according to the present invention

[0210] The solid sulfide electrolyte, solid halide electrolyte, and cathode composite were prepared as described above for Comparative Example 1.

[0211] Atomic Layer Deposition

[0212] Nano-thick Li3PO4 films were grown in a Picosun R200 Advanced ALD reactor at an argon pressure of approximately 2 mbar. Argon was used as carrier and purge gas.

[0213] Lithium tert-butyl oxide (LiOtBu) and trimethyl phosphate (TMPO) precursor were used as lithium and phosphate sources, respectively. LiOtBu precursor was purchased from Strem Chemicals (purity 98%), while TMPO precursor was purchased from Sigma-Aldrich (purity 99%). The sublimation temperatures were adapted to be 185°C and 85°C, respectively.

[0214] The temperature of the ALD reactor was set at 300°C and the growth rate was 0.6 Å / cycle. Thus 17 cycles were performed to obtain a 1 nm thick buffer layer.

[0215] TMPO and subsequently LiOtBu were alternately pulsed into the chamber with pulse times of 6 s and 3 s, respectively, separated by an 8 s argon purge.

[0216] Li6PS5Cl solid electrolyte pellets were obtained, with two opposite sides coated with Li3PO4.

[0217] Battery Pack Assembly

[0218] The battery pack assembly was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0219] The two-electrode cell was assembled as follows.

[0220] 16 to 18 mg / cm 2 The cathode composite material (NMC622 / Li3InCl6 / VGCF) was spread onto the first Li3PO4-coated surface of the Li6PS5Cl solid electrolyte pellets, and then Li 0.5 A mixture of In and Li6PS5Cl (in a weight ratio of 60:40) was added to the opposite Li3PO4 coated side of the Li6PS5Cl solid electrolyte pellets as a counter electrode.

[0221] Finally, the entire stack is further heated to 4 t / cm 2 Densification for 15 minutes. After compression, 1t / cm 2of pressure was applied to the fully assembled cell for electrochemical studies.

[0222] All assembly procedures were performed in a glove box under argon atmosphere ([O 2 ]<1 ppm, [H 2 O]<1 ppm).

[0223] Embodiment 3 according to the present invention

[0224] The solid sulfide electrolyte, solid halide electrolyte, and cathode composite were prepared as described above for Comparative Example 1.

[0225] Atomic Layer Deposition

[0226] Nano-thick Al2O3 films were grown in a Picosun R200 Advanced ALD reactor at an argon pressure of about 2 mbar. Argon was used as carrier and purge gas.

[0227] Trimethylaluminum (TMA) and ozone (O3) precursors were used as aluminum and oxygen sources, respectively. TMA precursor was purchased from STREM Chemical (purity 98%), while O3 precursor was synthesized by using a mixture of 99.5% O2 and 0.5% N2 using an ozone AC series generator model AC-Bench 2025 (from In USA).

[0228] The temperature of the ALD reactor was set at 150°C and the growth rate was 1.4 Å / cycle. Thus 7 cycles were performed to obtain a 1 nm thick buffer layer.

[0229] TMA and O3 were alternately pulsed into the chamber with pulse times of 0.3 sec and 0.5 sec, respectively, separated by a 5 sec argon purge.

[0230] Li6PS5Cl solid electrolyte pellets were obtained, one side of which was coated with Al2O3.

[0231] Battery Pack Assembly

[0232] The battery pack assembly was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0233] The two-electrode cell was assembled as follows.

[0234] 16 to 18 mg / cm 2 The wide cathode composite (NMC622 / Li3InCl6 / VGCF) was spread onto the Al2O3-coated surface of the Li6PS5Cl solid electrolyte pellets, and then Li 0.5A mixture of In and Li6PS5Cl (in a weight ratio of 60:40) was added to the uncoated side of the Li6PS5Cl solid electrolyte pellets as a counter electrode.

[0235] Finally, the entire stack is further heated to 4 t / cm 2 Densification for 15 minutes. After compression, 1t / cm 3 of pressure was applied to the fully assembled cell for electrochemical studies.

[0236] All assembly procedures were performed in a glove box under argon atmosphere ([O 2 ]<1 ppm, [H 2 O]<1 ppm).

[0237] Comparative Example 3

[0238] The solid sulfide electrolyte, solid halide electrolyte, and cathode composite were prepared as described above for Comparative Example 1.

[0239] Atomic Layer Deposition

[0240] Nano-thick Al2O3 films were grown in a Picosun R200 Advanced ALD reactor at an argon pressure of about 2 mbar. Argon was used as carrier and purge gas.

[0241] Trimethylaluminum (TMA) and ozone (O3) precursors were used as aluminum and oxygen sources, respectively. TMA precursor was purchased from STREM Chemical (purity 98%), while O3 precursor was synthesized by using a mixture of 99.5% O2 and 0.5% N2 using an ozone AC series generator model AC-Bench 2025 (from In USA).

[0242] The temperature of the ALD reactor was set at 150°C with a growth rate of 1.4 Angstroms / cycle. 71 cycles were thus performed to obtain a 10 nm thick buffer layer.

[0243] TMA and O3 were alternately pulsed into the chamber with pulse times of 0.3 sec and 0.5 sec, respectively, separated by a 5 sec argon purge.

[0244] Li6PS5Cl solid electrolyte pellets were obtained, coated on one side with a 10 nm thick Al2O3 buffer layer.

[0245] Battery Pack Assembly

[0246] The battery pack assembly was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0247] The two-electrode cell was assembled as follows.

[0248] 16 to 18 mg / cm 2 The cathode composite material (NMC622 / Li3InCl6 / VGCF) was spread onto the Al2O3-coated surface of the Li6PS5Cl solid electrolyte pellets, and then Li 0.5 A mixture of In and Li6PS5Cl (in a weight ratio of 60:40) was added to the uncoated side of the Li6PS5Cl solid electrolyte pellets as a counter electrode.

[0249] Finally, the entire stack is further heated to 4 t / cm 2 Densification for 15 minutes. After compression, 1t / cm 2 of pressure was applied to the fully assembled cell for electrochemical studies.

[0250] All assembly procedures were performed in a glove box under argon atmosphere ([O 2 ]<1 ppm, [H 2 O]<1 ppm).

[0251] Electrochemical testing

[0252] For all examples, electrochemical testing was performed in a cell consisting of a cylindrical polyetherimide (PEI) cell body and two 8 mm diameter stainless steel pistons.

[0253] Unless otherwise stated, all electrochemical cycling procedures were performed at room temperature under argon atmosphere in a glove box ([O 2 ] <1 ppm, [H 2 O] <1 ppm).

[0254] Conductivity measurement

[0255] Ionic conductivity measurements were performed by electrochemical impedance spectroscopy (EIS) at OCV, applying an excitation amplitude of 50 mV in the frequency range between 7 MHz and 1 Hz with 15 points per decade, using an MTZ impedance analyzer (BioLogic).

[0256] The results for a 1 nm thick Li3PO4 buffer layer are shown in Figure 2 , which shows that the presence of the buffer layer still enables lithium ion conduction while providing slight resistance.

[0257] Figure 6 It shows that the 10nm thick Li3PO4 buffer layer ( Figure 6 a) and Al2O3 buffer layer ( Figure 6 b) results in resistances greater than 300 kΩ and greater than 150 kΩ, respectively.

[0258] Therefore, a buffer layer of at least 10 nm results in poor ionic conductivity and thus unsatisfactory ASSB.

[0259] Constant current cycle

[0260] Galvanostatic cycling studies were performed at room temperature at C / 20 (C corresponds to 1 mol Li / mol active material in 1 h). All electrochemical measurements were performed with a VMP3 potentiostat / galvanostat (BioLogic) controlled by EC-Lab software.

[0261] Figure 3 The battery stack according to Example 1 of the present invention is described at 2.1 and 3.6 / 3.7 / 3.8 V vs. LiIn / In (2.7 and 4.2 / 4.3 / 4.4 V vs. LI + For the batteries with 2nm and 1nm thick buffer layers, the first cycle curve is Figure 3 a) and 3c), while the capacity retention is reported in Figure 3 b) and 3d). These figures demonstrate the low irreversible capacity and low polarization after the initial cycles, as well as the stable capacity retention during cycling, for both buffer layer thicknesses.

[0262] Figure 5 The cycling performance of the battery stack according to Example 2 of the present invention at 2.1-3.6V vs. LiIn / In is described. The cycling curves are Figure 5 a), while the capacity retention rate after 60 cycles is Figure 5 b). These figures also show low irreversible capacity and low polarization after the initial cycles and stable capacity retention during cycling for cells containing two buffer layers.

[0263] Figure 4 The cycling performance of a cell stack according to Comparative Example 1, i.e. without a buffer layer, under the same conditions as the embodiments according to the invention is described. The first cycle curves are reported at Figure 4 a), while the capacity retention is reported in Figure 4 b). These figures demonstrate that, in the absence of a buffer layer, the cell exhibits significant capacity decay during cycling. This decay is associated with the interfacial roadblock formed due to the lack of a buffer layer. It is demonstrated that this decay is not due to the cell setup, as it allows testing the cycling performance of the material in an ambient atmosphere that provides airtightness.

[0264] Figure 7 The cycling performance of the battery stacks according to Comparative Examples 2 and 3, i.e., including a 10 nm thick Li3PO4 buffer layer ( Figure 7 a) or Al2O3 buffer layer ( Figure 7 b) These figures show that with a buffer layer at least 10 nm thick, when current is applied to the cell, the potential measured is the open circuit voltage (OCV). Figure 6 As shown, this is due to the very low conductivity of the solid electrolyte and the 10 nm thick buffer layer.

[0265] These results demonstrate that the assembly according to the invention that can be assembled into an ASSB according to the invention allows obtaining satisfactory ionic conduction while mitigating the consequences of the relative instability of the different components of the ASSB towards each other, i.e. maintaining a stable capacity during the life of the assembly or of an ASSB containing it.

Claims

1. An all-solid-state battery pack, comprising: - an anode comprising an anode active material and a first solid electrolyte, - a cathode composite material comprising a cathode active material and a second solid electrolyte, - a solid electrolyte comprising a solid electrolyte material selected from the group consisting of a first and a second solid electrolyte, and at least one buffer layer, in particular one or two buffer layers, which are in contact with the surface of the solid electrolyte material, wherein When the solid electrolyte material is a first solid electrolyte, there is a buffer layer at the interface between the electrolyte and the cathode composite material, and When the solid electrolyte material is a second solid electrolyte, there is a buffer layer at the interface between the electrolyte and the anode, wherein the first electrolyte is selected from a sulfide solid electrolyte and a lithium oxide solid electrolyte, wherein the second electrolyte is a halide solid electrolyte, and The thickness of the buffer layer is 0.5 to less than 10 nm.

2. A component comprising: - a solid electrolyte comprising a solid electrolyte material selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte and a lithium oxide solid electrolyte, and at least one buffer layer, in particular one or two buffer layers, which are in contact with the surface of the solid electrolyte material, The thickness of the buffer layer is 0.5 to less than 10 nm.

3. A component comprising: - an anode comprising an anode active material and a solid electrolyte selected from a sulfide solid electrolyte and a lithium oxide solid electrolyte, and - a buffer layer in contact with the surface of the anode composite, The thickness of the buffer layer is 0.5 to less than 10 nm.

4. A component comprising: - a cathode composite material comprising a cathode active material and a halide solid electrolyte, and - a buffer layer in contact with the surface of the cathode composite material, The thickness of the buffer layer is 0.5 to less than 10 nm.

5. The all-solid-state battery pack according to claim 1 or the assembly according to claim 3, wherein: The negative electrode active material is selected from: - oxides, - nitrides, - Carbon such as natural graphite, coke, grown carbon, carbon fiber, spherical carbon, artificial graphite and amorphous carbon, - metals such as silicon, tin, sodium or lithium, their compounds and their alloys, In particular, the anode active material is selected from silicon, tin, lithium, their compounds and their alloys, such as Li x In y , wherein x is 0 to 1, and y is 0 to 1, preferably the anode active material is Li 0.5 In.

6. The all-solid-state battery pack according to any one of claims 1 and 5 or the assembly according to any one of claims 3 and 5, wherein: The anode comprises: - 50 to 70 wt%, and preferably 60 wt% Li 0.5 In, and - 30 to 50 wt %, and preferably 40 wt % of a sulfide solid electrolyte.

7. The all-solid-state battery according to any one of claims 1, 5 and 6 or the assembly according to claim 4, wherein the cathode active material is selected from doped or undoped, coated or uncoated transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluoride oxides, transition metal oxysulfides, transition metal oxynitrides and lithium-containing transition metal oxides, in particular, the cathode active material is a transition metal oxide, such as lithium cobalt oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese cobalt oxide, preferably having the formula LiNi 0.6 Mn 0.2 Co 0.2 O2.

8. The all-solid-state battery pack according to any one of claims 1 and 5 to 7 or the assembly according to any one of claims 4 or 7, wherein: The cathode composite material comprises: 55 to 75% by weight, in particular 60 to 70% by weight and preferably 66.7% by weight of cathode active material, 20 to 40% by weight, in particular 25 to 30% by weight, and preferably 28.6% by weight of a halide solid electrolyte, and optionally 1 to 10% by weight, in particular 2 to 7% by weight and preferably 4.8% by weight, of an electron-conducting carbon compound.

9. An all-solid-state battery according to any one of claims 1 and 5 to 8 or a component according to any one of claims 3 to 8, wherein the at least one electrode comprises an electronic conductor compound selected from natural or artificial graphite, graphene, carbon nanotubes, acetylene black, Ketjen black, activated carbon, carbon fluoride, metal powder, conductive whisker, conductive metal oxide, conductive polymer, metal fiber or carbon fiber, preferably, the electronic conductor is vapor-grown carbon fiber.

10. The all-solid-state battery according to any one of claims 1 and 5 to 9 or the assembly according to any one of claims 2, 4 and 7 to 9, wherein the halide solid electrolyte has the formula M 3-z (Me k+ ) f X 3-z+k*f Where -3≤z≤3, 2≤k<6, 0≤f≤1; - M includes alkali metal elements, especially Li; -Me includes divalent, trivalent, tetravalent, pentavalent or hexavalent metal elements or any combination thereof, in particular Me is selected from: i. Alkaline earth metals, including Ba, Mg, Ca, Sr, ii Rare earth elements, such as Y, Sc, Ce, Gd, Er, La, Yb and combinations thereof, iii.3d transition metals such as Zn, Cu, V and iv. an element selected from the group consisting of Zr, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, Te, In, Bi, Al, Ga, and v. any combination thereof, and -X is halogen, in particular selected from Cl, Br, I and any combination thereof; Preferably, the halide solid electrolyte is Li3InCl6.

11. The all-solid-state battery according to any one of claims 1 and 5 to 10 or the assembly according to any one of claims 2, 3 to 6 and 9, wherein the sulfide solid electrolyte is selected from the formula Li 7-x PS 6-x X x Thiophosphate and argyrodite, wherein 0≤X≤2, and X is a halide, in particular selected from Cl, Br and I, preferably the first solid electrolyte is selected from argyrodite, and even more preferably Li6PS5Cl.

12. The all-solid-state battery pack according to any one of claims 1 and 5 to 11 or the assembly according to any one of claims 2, 3 to 6, 9 and 11, wherein: The lithium oxide solid electrolyte is selected from NASICON such as LiTi2(PO4)3; perovskite such as (LaLi)TiO3; LISICON such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; garnet such as Li7La3Zr2O 12 , in particular the lithium oxide solid electrolyte is garnet, preferably Li7La3Zr2O 12 .

13. The all-solid-state battery pack according to any one of claims 1 and 5 to 12 or the assembly according to any one of claims 2 to 12, wherein: The buffer layer has a thickness of 0.75 nm to 5 nm, and preferably 1 nm to 2 nm.

14. The all-solid-state battery according to any one of claims 1 and 5 to 13 or the assembly according to any one of claims 2 to 13, wherein: The buffer layer comprises a buffer material, in particular, consists of a buffer material, wherein the buffer material is selected from lithium phosphate, such as Li3PO4 or lithium phosphorus oxynitride; lithium nitride; NASICON such as LiTi2(PO4)3; perovskite, such as (LaLi)TiO3; LISICON, such as Li 14 ZnGe4O 16 , Li4SiO4 or LiGeO4; garnet such as Li7La3Zr2O 12 and Al2O3, more particularly the buffer layer comprises Li3PO4 or Al2O3, particularly consisting thereof; preferably, the buffer layer comprises Li3PO4, particularly consisting thereof.

15. A method of manufacturing an all-solid-state battery according to any one of claims 1 and 5 to 14 or an assembly according to any one of claims 2 to 14, wherein: The buffer layer is deposited onto at least one substrate selected from the group consisting of a solid electrolyte, an anode composite and a cathode composite by a vapor deposition based method, such as physical vapor deposition, chemical vapor deposition or by atomic layer deposition, preferably by atomic layer deposition.

16. The method of claim 15, wherein the buffer layer is deposited on a powder substrate or on a dense substrate.

17. The method according to any one of claims 15 or 16, wherein the buffer layer is deposited by atomic layer deposition, and the atomic layer deposition reactor is set at the following temperature: -85°C to 185°C, particularly 100°C to 170°C, and preferably 150°C, or -200°C to 400°C, particularly 250°C to 350°C, and preferably at 300°C.

Citation Information

Cited By

  • Inorganic-organic composite solid electrolyte, membrane material thereof, preparation method and solid-state battery

    CN120709490A

  • Inorganic-organic composite solid electrolyte, film material thereof, preparation method and solid-state battery

    CN120709490B

  • Silicon-carbon composite material with in-situ generated double-layer skeleton structure, and preparation method and application thereof

    CN121054658A

  • Silicon-carbon composite material with double-layer skeleton structure generated in situ, and preparation method and application thereof

    CN121054658B

  • Modified negative electrode current collector and preparation method and application thereof

    CN121282205A